Sensory, biochemical and microbiological changes of farmed catfish (Clarias batrachus, Linnaeus) and red tilapia (Oreochromis sp.) at Ambient Storage - Bakar, Jamilah; Ahmad, Nurul Izzah (Universiti Putra Malaysia Press, 1995)
Farmed catfish (Clarias batrachus, Linnaeus) and red tilapia (Oreochromis sp.) were stored at ambient temperature (28±2°C) for a period of 24 h. They were evaluated for acceptability, freshness deterioration, rancidity development and microbiological changes. Raw catfish was acceptable up to 20 h and that of tilapia up to 15 h. Upon rejection their KJ values were 70.0 and 42.7% for tilapia and catfish respectively. Microbiologically, catfish samples did not exceed the 107 cfu/g limit until the end of the storage period; however, tilapia was not acceptable by the 20th hour.